Efektivitas Pelaksanaan Penagihan Pajak Aktif Dalam Pencairan Tunggakan Pajak - Choirun Nissa; Muslimin Muslimin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to test and analyze the effectiveness of the implementation of active tax collection in tax arrears. The object of this research is the billing performance. And the informants in this research are Mr. Mudiantoro and Mr. Wildan Wijaya who are related to the KPP Pratama Surabaya Mulyorejo. The subject of this research is the tax revenue report, as well as other data for 2018-2020. The research uses an interactive model, whose elements include data reduction (data reduction), data display (data display), and drawing/verifying conclusions. The type of data used in this research is qualitative. The results of this study indicate that the state of active tax collection with letters as billing actions issued is still experiencing ups and downs so that it can be said that taxpayers are not fully aware of their tax obligations, tax collection reports with warning letters in 2018-2020 are still classified as ineffective, Tax collection reports with forced letters in 2018-2020 are still classified as ineffective. Keywords: active tax collection, taxpayer, tax collection report